THE EFFECT OF MENTAL HEALTH INFORMATION QUALITY AND MESSAGE RELEVANCE ON SELF-DIAGNOSIS ON THE @sakti_mikaeel TIKTOK ACCOUNT - Devi Mulyanti; Rita Destiwati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Self-diagnosis of mental health disorders, particularly Attention Deficit Hyperactivity Disorder (ADHD), has become an increasingly prominent phenomenon among Generation Z, especially through social media platforms such as TikTok. This study aims to examine the influence of information quality and message relevance on the self-diagnosis behavior of followers of the TikTok account @sakti_mikaeel, using the Uses and Gratifications theory as a theoretical framework. A quantitative approach was employed through a survey method, analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software. The study involved 400 respondents, all of whom were followers of the account, with the majority aged between 17 and 25 years and predominantly students. The results indicate that information quality and message relevance simultaneously have a significant influence on self-diagnosis behavior, with a moderate effect size of 58.1%, while the remaining 41.9% is influenced by other factors not examined in this study. The accuracy dimension of information quality and the benefit dimension of message relevance emerged as dominant contributors to increased self-reflection and personal identification among respondents. These findings highlight that social media is not merely an information source, but also a dynamic psychological space that facilitates perception, introspection, and personal conclusions regarding mental health. This research expands the application of the Uses and Gratifications theory within the context of digital mental health and offers practical implications for the ethical, educational, and responsible management of mental health content on social media platforms.